Effect of mixtures of essential oils of citrus species on the control of Colletotrichum gloeosporioides (Research, Society and Development, 2020)
This work evaluates the fungitoxic potential of essential oils blends of lemon 'Thaiti', sweet orange, and mandarin on Colletotrichum gloeosporioides. The experiments occurred in a completely randomized design in a 7x8+2 factorial scheme, with seven formulations of essential oils (4 mixtures and 3 pure essential oils used as comparatives) in eight concentrations each (0.0125, 0.025, 0.05, 0.1, 0.2, 0.25, 0.5, and 1.0%), one negative control (0.0%), and one positive control (commercial Thiram fungicide at the concentration recommended by the manufacturer - 1 mL L-1), with 5 repetitions each. The different treatments were incorporated into PDA culture medium (Potato Dextrose Agar) and poured into Petri dishes. The plates containing the treatments were inoculated with C. gloeosporioides and incubated for seven days at 27±2°C. Growth was measured daily to calculate the percentage of mycelial growth inhibition and the mycelial growth rate index. All concentrations of citrus essential oils and the blends inhibited the mycelial growth of C. gloeosporioides. The pure essential oils of lemon, orange, and tangerine provided the greatest inhibitions, with average values of 67.7, 56.1, and 55.9%, respectively. The blends promoted lower inhibitions than the treatment with the commercial fungicide. We recommend to carry out in vivo tests to verify if the blends of citrus essential oils have better control over the growth of C. gloeosporioides under field conditions.